Audiological and Other Factors Predicting the Presence of Misophonia Symptoms Among a Clinical Population Seeking Help for Tinnitus and/or Hyperacusis - Aazh, Hashir; Erfanian, Mercede; Danesh, Ali A.; Moore, Brian C. J. (Frontiers in Neuroscience, 2022)
This paper evaluates the proportion and the audiological and other characteristics of patients with symptoms of misophonia among a population seeking help for tinnitus and/or hyperacusis at an audiology clinic (n = 257). To assess such symptoms, patients were asked “over the last 2 weeks, how often have you been bothered by any of the following problems? Feeling angry or anxious when hearing certain sounds related to eating noises, lip-smacking, sniffling, breathing, clicking sounds, tapping?”. The results of routine audiological tests and self-report questionnaires were gathered retrospectively from the records of the patients. Measures included: pure tone audiometry, uncomfortable loudness levels (ULLs), and responses to the tinnitus impact questionnaire (TIQ), the hyperacusis impact questionnaire (HIQ), and the screening for anxiety and depression in tinnitus (SAD-T) questionnaire. The mean age of the patients was 53 years (SD = 16) (age range 17 to 97 years). Fifty four percent were female. Twenty-three percent of patients were classified as having misophonia. The presence and frequency of reporting misophonia symptoms were not related to audiometric thresholds, except that a steeply sloping audiogram reduced the likelihood of frequent misophonia symptoms. Those with more frequent misophonia symptoms had lower values of ULLmin (the across-frequency average of ULLs for the ear with lower average ULLs) than those with less frequent or no reported symptoms. The reported frequency of experiencing misophonia symptoms increased with increasing impact of tinnitus (TIQ score ≥9), increasing impact of hyperacusis (HIQ score >11), and symptoms of anxiety and depression (SAD-T score ≥4). It is concluded that, when assessing individuals with tinnitus and hyperacusis, it is important to screen for misophonia, particularly when ULLmin is abnormally low or the TIQ, HIQ or SAD-T score is high. This will help clinicians to distinguish patients with misophonia, guiding the choice of therapeutic strategies.